Measurement of pure shear constitutive relationship from torsion tests under quasi-static, medium, and high strain rate conditions - Zhang, L; Townsend, D; Petrinic, N; Pellegrino, A (American Society of Mechanical Engineers, 2021)
Torsion tests provide important shear stress and shear strain relationships to reveal the fundamental plastic flow response of a material. Bespoke torsion techniques complemented by digital image correlation are developed to accurately measure the shear stress–strain relationship at quasi-static, medium rate 9/s, and high strain rate above 1000/s. The equipment used includes a screw-driven mechanical system, a hydraulic Instron machine and a Campbell thin-walled tube split Hopkinson torsion bar equipped with an ultrahigh-speed camera. A near alpha Ti3Al2.5V alloy was used as a model material in this study. A four-camera digital image system has been constructed to monitor the material deformation and failure during a low rate torsion test, to gain further insight into plastic deformation of the tubular specimen. Shear stress–strain relationship of the Ti3Al2.5V alloy exhibits noticeable strain rate sensitivity. Observations of the strain hardening rate evolution indicate that the hardening capacity of Ti3Al2.5V is both strain and strain rate dependent. High strain rate torsional stress–strain relationship shows lower strain hardening, compared to the response obtained from a shear compression specimen. The present techniques are demonstrated to be suitable for the measurement of pure shear constitutive relationship, including rate sensitivity and failure of the material.